The effects of medium nutritional profile on Bacillus sp. Par 3 plant-growth promoting and biocontrol activity against Botrytis cinerea - Dujković, Tatjana; Pajčin, Ivana; Vlajkov, Vanja; Šovljanski, Olja; Markov, Siniša; Loc, Marta; Grahovac, Mila; Grahovac, Jovana (Pesticides and Phytomedicine / Pesticidi i fitomedicina, 2023)
Substantial agricultural losses resulting from plant diseases caused by different plant pathogens are one of the worldwide challenges today. Among these, Botrytis cinerea, responsible for gray mold disease, stands out for its capacity to devastate significant quantities of diverse valuable crops. Utilization of biocontrol agents for suppressing phytopathogens has become imperative, and bacteria from the genus Bacillus hold an immense potential due to their rapid replication rate, resistance to adverse environmental conditions, enhanced effectiveness in promoting plant growth and broad-spectrum activity. The objective of this study was to determine the best sources of carbon, nitrogen and phosphorus in cultivation media with the aim of maximizing both antimicrobial activity against B. cinerea and plant growth-promoting (PGP) potential during the early stages of cucumber plant development, exhibited by Bacillus sp. isolate Par 3. Antimicrobial activity was tested using the well diffusion method. The influence of Bacillus sp. isolate Par 3 on plant germination was tested on cucumber seeds. The largest inhibition zones were achieved in two cases, with 1) sucrose as carbon source, ammonium nitrate as nitrogen source, and diammonium hydrogen phosphate as phosphorus source and 2) glycerol as carbon source, ammonium nitrate as nitrogen source and dipotassium hydrogen phosphate as phosphorus source. Seeds treated with a culture liquid of Bacillus sp. isolate Par 3 using the optimized medium exhibited the best results in terms of cucumber germination percentage (100%), root length (53.09 mm) and shoot length (13.26 mm). Bacillus sp. Par 3 isolate was identified as Bacillus subtilis using 16S rRNA gene sequencing. The results of this study underscore the significance of media optimization for the production of biocontrol agents, taking into account both antimicrobial efficacy and PGP characteristics.